Improving water productivity, reducing poverty and enhancing equity in mixed crop-livestock systems in the Indo-Gangetic Basin - Clement, Floriane; Haileslassie, Amare; Ishaq, S.; Samad, M.; Mit, R.; Shindey, D.N.; Dey, A.; Khan, M.A.; Blümmel, Michael; Acharya, Sreedhar; Radha, A.Venkata (CGIAR Challenge Program on Water and Food, 2010)
The “Improving water productivity, reducing poverty and enhancing equity in mixed crop-livestock systems in the Indo-Gangetic Basin” was designed and conducted by the International Water Management Institute (IWMI), in partnership with international and national partners, to address the relative neglect of livestock water needs of crop-livestock farming systems. The primary objective of this project was to optimize the productive use of water in the crop-livestock farming systems of semi-arid areas to enhance livelihoods, reduce poverty, contribute to gender equity, and protect the environment. This was addressed through an integrated approach led by a multi-disciplinary team across three States of the Ganga Basin.